The cells at work animation improves students' analytical skills in learning the circulatory system - Syadella, Femi; Ahmad, Intan; Hizqiyah, Ida Yayu Nurul; Gurnita, Gurnita (Universitas Wiralodra, 2025)
Analytical skills are one of the essential skills that high school students must possess and are listed in the curriculum. Analytical skills are included in category C4 in Bloom's taxonomy. However, many students still lack this ability. This is influenced by several factors, one of which is the type of learning media. This study aims to evaluate the effectiveness of the Cells at Work animation as a learning medium for biology, with a focus on the material related to the circulatory system. The method used is a pre-experimental design with a one-group pre-test-post-test model, conducted on class XI- MIPA 5 students at SMA Pasundan 2, Bandung. The results of the study showed that this animation media makes it easier for students to understand the material due to its attractive visual and audio displays. This can be seen from the increase in the average student score, namely from 56 at the pre-test to 83 at the post-test, with the percentage of mastery of all indicators reaching 83%. Thus, the Cells at Work animation is effective for use as a learning medium in biology, especially for material related to the circulatory system. This study provides empirical evidence that animated media with contextual content, such as Cells at Work, can significantly enhance analytical thinking skills in science learning, particularly for complex topics like the circulatory system.